Tantangan Sekolah Kristen Masa Kini: Amanat Agung Dan Eksklusifisme - Yohana Indah Kristianingrum; Jos Sudarman Lauwanto; Andreas Fernando (Shalom: Jurnal Teologi Kristen, 2023)
Christian schools are unique institutions because they can play a dual role in both the educational and spiritual fields effectively. However, in today's educational development, Christian schools are less able to carry out this dual role. In this discussion, the authors observe that several studies reveal that the dual role of Christian schools tends to become exclusive educational institutions with superior and advanced quality education, but are unable to educate students according to the Great Commission of the Lord Jesus. The challenge for today's Christian schools is the difficulty of implementing the Great Commission because they focus more on competition between schools in order to increase school prestige. The method used by the author is literature research, by analyzing and comparing several writings that discuss the topic. The results of this study found a suggestion for Christian schools to return to their original vision, namely to become God's agents to make disciples or bring their students to a real encounter with Him. One of its concrete missions is to provide opportunities for underprivileged children to be able to receive education in Christian schools     Abstrak Sekolah Kristen merupakan lembaga yang unik karena dapat berperan ganda baik dalam bidang pendidikan maupun bidang kerohanian secara efektif. Namun dalam perkembangan pendidikan masa kini sekolah Kristen kurang mampu menjalankan peran ganda tersebut. Dalam pembahasan ini, penulis melihat beberapa kajian  mengungkapkan bahwa peran ganda sekolah Kristen  semakin cenderung menjadi lembaga pendidikan eksklusif dengan kualitas pendidikan yang unggul dan maju, tetapi tidak dapat memuridkan anak didik sesuai Amanat Agung Tuhan Yesus. Tantangan bagi sekolah Kristen masa kini adalah kesulitan menerapkan Amanat Agung dikarenakan lebih berfokus kepada persaingan prestasi antar sekolah guna menaikkan prestis sekolah. Metode yang dipakai oleh penulis adalah penelitian literatur, dengan menganalisa dan membandingkan beberapa tulisan yang membahas topik tersebut. Hasil dari kajian ini adalah ditemukan usulan agar sekolah Kristen mengembalikan kepada visi yang semula yaitu menjadi agen Tuhan untuk memuridkan atau membawa anak didik kepada perjumpaan nyata dengan-Nya. Salah satu misi konkritnya adalah dengan memberikan kesempatan dan kemudahan kepada anak-anak kurang mampu untuk dapat mengenyam pendidikan di sekolah Kristen.